A Comprehensive Evaluation of the Genetic Relatedness of Listeria monocytogenes Serotype 4b Variant Strains - Burall, Laurel S.; Grim, Christopher J.; Mammel, Mark K.; Datta, Atin R. (Frontiers in Public Health, 2017)
Recently, we have identified a link between four listeriosis incidents/outbreaks to a variant of Listeria monocytogenes serotype 4b strains, 4bV. Although 4bV strains have been reported from clinical specimens as well as from foods, listeriosis outbreaks occurring in 2014 – 2016 were the first reported outbreaks involving 4bV in the USA. Since traditional typing methods do not detect members of this group, we undertook a systematic and retrospective analysis of all Listeria monocytogenes in the NCBI WGS sequence read archive database in order to investigate the burden of 4bV strains among all listeriosis cases. This analysis identified the presence of isolates causing sporadic cases as well as those associated with the aforementioned outbreaks, as determined by WGS and traditional epidemiology. In total, approximately 350 L. monocytogenes 4bV strains were identified from multiple parts of the US as well as from Australia and Chile, dating back to 2001. The genomic relatedness of these strains was compared using the CFSAN SNP Pipeline and Multi Locus Virulent Sequence Typing (MVLST). Using the CFSAN Pipeline tool, the 4bV strains were found to group into seven clusters that were separate from 4b strains. All seven clades appeared to contain isolates from both clinical and non-clinical sources. Conversely, the MVLST analysis revealed that practically all of the strains belonged to a single clade, suggesting that 4bV strains from disparate geographic regions and sources are under varied selective pressure, restricting diversity across these six virulence loci while allowing more variability across the genome as a whole. Further evaluation of these 4bV strains identified genes potentially acquired from a lineage II source external to the lmo0733-lmo0739 region, as well as highly conserved SNPs unique to the 4bV strains when compared to those from other lineages. Taken together this data suggests that 4bV strains have undergone adaptive responses to selective pressures that may enhance survival in the environment while maintaining the pathogenic potential of serotype 4b strains.